2012
DOI: 10.1093/icvts/ivs050
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation for bleeding in cardiac surgery

Abstract: At Odense University Hospital (OUH), 5-9% of all unselected cardiac surgical patients undergo reoperation due to excessive bleeding. The reoperated patients have an approximately three times greater mortality than non-reoperated. To reduce the rate of reoperations and mortality due to postoperative bleeding, we aim to identify risk factors that predict reoperation. A total of 1452 consecutive patients undergoing cardiac surgery using extracorporeal circulation (ECC) between November 2005 and December 2008 at O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 5 publications
1
62
1
8
Order By: Relevance
“…The prevalence of reoperation in our study group was 4.3% and was similar to that of previously reported articles [3,[8][9][10][11]. All patients were reoperated in the operating theater.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of reoperation in our study group was 4.3% and was similar to that of previously reported articles [3,[8][9][10][11]. All patients were reoperated in the operating theater.…”
Section: Discussionsupporting
confidence: 90%
“…They recommended that surgeries be planned carefully in patients with a high EuroSCORE, low ejection fraction (EF), low BMI, DM, preoperative s-creatinine >134 µmol/l or for procedures other than CABG. 26) In our study, a few cases required reoperation (low and normal weight, 1.2%; overweight patients, 0.6%; none among obese) and no significant differences were found between groups. Other studies have investigated the effect of obesity on surgical outcomes.…”
Section: Discussionmentioning
confidence: 42%
“…18,24) Deciding when a patient requires transfusion varies significantly among intensivists, anesthetists, and cardiac surgeons. 18,25,26) The use of blood and other blood product transfusions in cardiac surgical patients remains very high. 29) This large-scale study after primary CABG was conducted among exclusively ethnic Chinese and found lower blood loss and transfusion with elevated BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Re-thoracotomy for post-operative haemorrhage is a well known complication in cardio-thoracic surgery [6,7]. In thoracic surgery the reported incidence of re-exploration for bleeding ranges from 1 to 3.7% and the need for blood transfusion ranges from 20 to 52% in haemorrhagic patients [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5]. At the same time different studies have shown that re-exploration for bleeding has a negative impact on patient outcome, increasing the morbidity rate and in-hospital mortality [6,7]. The systemic infusion of antifibrinolytic agents has been used effectively to reduce post-operative blood loss and transfusion requirements in different kinds of surgical procedures bleeding diathesis (haemophilia, etc.…”
Section: Introductionmentioning
confidence: 99%